Use of aripiprazole for delirium in the elderly: a short review. Issue 1 (17th December 2014) - Kirino, Eiji
Abstract The effects and tolerability of antipsychotics in delirium treatment remain controversial. Compared to other antipsychotics, aripiprazole differs in pharmacological activity because it exerts its effect as a dopamine D2 partial agonist. The guidelines of the American Psychiatric Association rank aripiprazole highly among antipsychotics with regard to safety, and this drug is likely to be useful for delirium treatment. Here, we reviewed the efficacy and safety of aripiprazole for delirium. The results of our literature review on the efficacy and safety of delirium treatments suggest that aripiprazole is an effective treatment option for delirium in the elderly. Aripiprazole is as effective as other antipsychotics in improving delirium symptoms, and it is safer because it is less likely to cause extrapyramidal symptoms, excessive sedation, and weight gain. However, these findings are based on only a few clinical studies of elderly patients with delirium. Therefore, further investigations are necessary.